Cultural Harmony in The Florestycommunity in The Novel Sekaca Cempaka By Nailiya Nikmah JKF - Sri Normuliati; Jamiatul Hamidah; M. Ridha Anwari (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study aims to determine the cultural harmony in Nailiya Nikmah JKF's novel Sekaca Cempaka. The theory used in this research is literary ecology theory. The method in this research uses descriptive qualitative method with research data in the form of words, phrases, sentences, dialogue of the characters, and paragraphs in Nailiya Nikmah JKF's novel Sekaca Cempaka. The results showed that in the novel Sekaca Cempaka there is a relationship between community and nature, traditions that live in society, values ​​that are believed by community, and myths that develop in community.